I came across the following mathematical statement in a proof. Can somebody tell me which property of greatest integer function makes it possible?

$x + y - \lfloor x + y \rfloor + z - \lfloor x + y - \lfloor x + y \rfloor + z \rfloor = x + y - \lfloor x + y \rfloor + z - \lfloor x + y + z \rfloor + \lfloor x + y \rfloor$

How do we get $ \lfloor x + y - \lfloor x + y \rfloor + z \rfloor = \lfloor x + y + z \rfloor - \lfloor x + y \rfloor$?

Thanks in advance...


In general, if $N$ is an integer, then $$\lfloor N+\alpha\rfloor=N+\lfloor\alpha\rfloor.$$

Proof : Let $N+\alpha=M+\beta$ where $M$ is an integer and $0\le \beta\lt 1$. Then, since we have $$\alpha=M-N+\beta\Rightarrow \lfloor\alpha\rfloor=M-N,$$ we have $$\begin{align}\lfloor N+\alpha\rfloor&=\lfloor M+\beta\rfloor\\&=M\\&=N+(M-N)\\&=N+\lfloor\alpha\rfloor.\end{align}$$ Here, setting $N=-\lfloor x+y\rfloor,\alpha=x+y+z$ gives us $$\lfloor -\lfloor x+y\rfloor+(x+y+z)\rfloor=-\lfloor x+y\rfloor+\lfloor x+y+z\rfloor.$$

  • 1
    $\begingroup$ Thanks.....:) I don't know why it didn't occur me before... $\endgroup$ – Ritu Oct 16 '14 at 12:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.